THE INFLUENCE OF FINANCING MODEL AND CREDIT RISK ON FINANCIAL STABILITY (STUDY OF ISLAMIC RURAL BANKS IN JAVA ISLAND) - Addury, Multazam Mansyur; Ramadhani, Aprilia Kinasih Putri (Journal of Islamic Monetary Economics and Finance, 2024)
This study examines the impact of profit-sharing financing and profit-margin financing on financial stability of Islamic Rural Banks (IRBs) in Java Island and incorporates credit risk as an intervening variable. Utilizing a panel dataset of 90 registered IRBs operating in Java Island from 2011 to 2021 and applying path analysis, we find that profit margin financing has a significant negative impact on the financial stability of IRBs, both directly and indirectly through its association with credit risk. In contrast, profit sharing financing shows a positive and significant direct effect on financial stability. This result implies that profit margin financing may pose a greater risk to the financial stability of IRBs than profit-sharing financing. The study highlights the need for IRBs to carefully manage their financing strategies, taking into consideration the potential risks associated with profit margin financing. Effective risk management practices are crucial for mitigating credit risk and ensuring the overall stability of IRBs. The research emphasizes the importance of a selective approach in providing profit-sharing financing to mitigate potential risks. It also underscores the significance of striking a balance between profitability and credit risk management to ensure the long-term stability of IRBs.